THE IMPACT OF WORDS MAPPING TOWARD THE VOCABULARY MASTERY ON YOUNG LEARNERS AT MADRASAH IBTIDAIYAH MAUIZATUN HASANAH SCHOOL MUARO JAMBI - Ardan, Yuzaki; Failasofah, Failasofah (Magister Pendidikan Bahasa Inggris Universitas Jambi, 2024)
In this line the researcher tries to find some important points in this research which can be helpful in the future, the research objectives to be achieved is to find out whether there is Significant impact using words mapping towards vocabulary mastery on young learner at Madrasah Ibtidaiyah Mauizatun Hasanah School Muaro Jambi in the academic year 2022/2023.This study is experimental in nature and employs a quantitative methodology with two random groups for the pre- and post-tests. Images or photos are used in quantitative research to determine the current condition, which is then used to inform a descriptive study that provides an explanation of the issue after it has been identified.Data from the experimental class' pre-test show a result of 0,165, whereas data from the control class show a result of 0,174, and data from the experimental class''s post-test show a result of 0,081, as opposed to 0,200 for the control class''s data. All of the data used in this study were normal, it can be said.it can be concluded that word mapping approach was regarded as a useful strategy to enhance the students'' vocabulary mastery in relation to reading, writing, speaking and understanding about the meaning. It was in line with the word mapping strategy's purpose of helping students understand the material more easily while also training them to be more engaged and imaginative.